2022
DOI: 10.3389/fpsyg.2022.923027
|View full text |Cite
|
Sign up to set email alerts
|

Is good more alike than bad? Positive-negative asymmetry in the differentiation between options. A study on the evaluation of fictitious political profiles

Abstract: Our research focuses on the perception of difference in the evaluations of positive and negative options. The literature provides evidence for two opposite effects: on the one hand, negative objects are said to be more differentiated (e.g., density hypothesis), on the other, people are shown to see greater differences between positive options (e.g., liking-breeds-differentiation principle). In our study, we investigated the perception of difference between fictitious political candidates, hypothesizing greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Thirdly, we conducted only one study in which we investigated the relationship between objective and subjective similarity estimates and the effect of additional positive and negative features on similarity judgements. Although rather scarce on its own, the paper is a part of our string of publications on various instances of positive-negative asymmetry in similarity judgements ( Falkowski et al, 2018 , 2021 ; Falkowski and Jabłońska, 2018 ; Jablonska et al, 2022 ) and as such provides good evidence for the observed effects. Still, the comparison of normative predictions of the ratio model and subjective similarity estimates should be further verified on objects other than political candidates.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thirdly, we conducted only one study in which we investigated the relationship between objective and subjective similarity estimates and the effect of additional positive and negative features on similarity judgements. Although rather scarce on its own, the paper is a part of our string of publications on various instances of positive-negative asymmetry in similarity judgements ( Falkowski et al, 2018 , 2021 ; Falkowski and Jabłońska, 2018 ; Jablonska et al, 2022 ) and as such provides good evidence for the observed effects. Still, the comparison of normative predictions of the ratio model and subjective similarity estimates should be further verified on objects other than political candidates.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, two additional positive features, being more similar, may have provided less positive evidence that would prompt individuals to alter their appraisal of an unfavourable candidate compared to two more differentiated negative features that carried sufficient information to diminish the evaluation of a favourable candidate. Alternatively, the absence of an effect of additional positive features on similarity judgments can be attributed to a lesser differentiation between negative options compared to positive ones, which is the focus of our current research (Jablonska et al, 2022).…”
Section: The Effect Of Additional Positive and Negative Features On S...mentioning
confidence: 93%